Enabling Productive but Asset-Poor Farmers to Succeed : A Risk Financing Framework - Gurenko, Eugene (World Bank, Washington, D.C., 2013)
This paper examines how market-based risk financing instruments could enable asset-poor but productive farmers exposed to production shocks to engage in riskier but higher-return agricultural activities. The financing of these exogenous shocks is addressed in a conceptual framework based on an optimal allocation of capital where the farm is viewed as a business unit. The approach allows for (1) testing the business viability of a specified crop by assessing the minimum business capital required to ensure the continuity of the business after the occurrence of an adverse production shock; and (2) designing an optimal risk financing program to finance the minimum capital requirements using a combination of instruments (insurance, savings, and borrowing). The authors provide numerical and graphical examples to illustrate the relevance of this financial approach to the specific issues of agricultural risk management.